OPTIMASI FORMULASI SABUN CAIR ANTIBAKTERI VARIASI KOMBINASI EKSTRAK DAUN LEGUNDI DAN SIRIH - Ida Bagus Oka Suyasa; Putu Ayu Suryaningsih; Trisna Bagus Wibawa; Putu Diah Wahyuni; Ni Made Deliabudi Apriliapatni; I Made Krisna Paramartha; Pande Putu Wahyu Pradiptha Nugraha (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2023)
Background: Legundi leaves and betel leaves are widely known as plants that contain medicinal properties. The extract of these two leaves is useful as an antibacterial agent. Aims: This research was conducted with the aim of knowing the antibacterial activity of liquid soap containing the active ingredients of the two leaves. Method:The variables studied included: organoleptic properties, pH value, foam height, free alkali content, specific gravity and antibacterial activity. The type of research used istrue experimental research. The research design is Postes only control design. Data collection was carried out by means of measurement, while data analysis was in the form of descriptive and analytic. Conclucion:The conclusions obtained include liquid soap preparations in various combinations of legundi leaf and betel leaf extracts that meet SNI requirements, the bacterial inhibition zone is classified as strong but the most optimal is F3, there are differences in the diameter of the inhibition zone for Staphylococcus aureus bacteria growth in liquid soap with various combinations of extracts. The recommendations given for the research to continue up to the irritation test, it is necessary to add fragrances to make it more fragrant.